Postnatal growth and gut microbiota development influenced early childhood growth in preterm infants - Tadros, Jocelyne S.; Llerena, Amelia; Sarkar, Anujit; Johnson, Reynold; Miller, Elizabeth M.; Gray, Heewon L.; Ho, Thao T. B. (Frontiers in Pediatrics, 2022)
Background: Preterm infants are at high risk for growth failure and childhood weight problems due to the disruption of normal intrauterine growth and nutrition. Early nutritional support and microbiome acquisition can play an important role in childhood growth. Objective: Our study examined potential postnatal indicators, including gut bacterial compositions, macronutrients, and catch-up growth, of growth pattern from infancy into early childhood. Methods: This is a retrospective study of preterm infants born <35 weeks who were followed up in the university complex care clinic from 2012-2018. Weight and length z-scores at birth, 1, 2, 4, 6, 12 and 15 months, and body mass index (BMI) and length z-scores from 2 to 5 years of age were collected. Catch-up growths were calculated by changes in z-scores and divided into early (birth-4 months) and late (4-18 months). Postnatal nutritional data and fecal samples were collected. Fecal microbiome data obtained from 16S RNA V4 sequencing was analyzed against clinical and growth data using a regression model. Results: 160 infants included in the final analysis had birth weight and gestational age of 1149 ± 496 grams and 28 ± 3 weeks. Early weight gain positively correlated with length z-scores but not with BMI at 2 years of age. BMI at 2 years of age strongly correlated with BMI at 3, 4, and 5 years of age. Postnatal abundance of Gammaproteobacteria was negatively associated with early growth while Bacteroides and Lactobacillus were positively associated with childhood BMI. Conclusion: Our findings suggest that optimal postnatal nutrition promoted early catch-up growth in weight as well as improved linear growth without influence on childhood BMI. Postnatal gut microbial colonization, which is a modifiable factor, was associated with childhood growth in preterm infants.